Enhanced Recovery after Elective Open Surgical Repair of Abdominal Aortic Aneurysm: A Complementary Overview through a Pooled Analysis of Proportions from Case Series Studies - Gurgel, Sanderland J. T. [UNESP]; El Dib, Regina [UNESP]; Nascimento, Paulo do [UNESP] (Public Library Science, 2014)
Objectives: To evaluate the efficacy and safety of enhanced recovery after surgery (ERAS) programs in elective open surgical repair (OSR) of abdominal aortic aneurysm (AAA).Background: Open surgical repair of AAA is associated with high morbidity and mortality, prolonged hospital stay and high costs. ERAS programs contribute to the optimization of treatment by reducing hospital stay and improving clinical outcomes.Methods: A review of PubMed, EMBASE and LILACS databases was conducted. As only one randomized controlled trial was found, a pooled analysis of proportions from case series was conducted, considering it a complementary overview of the topic. Inclusion criteria were case series with more than five cases reported, adult patients who underwent an elective OSR of AAA and use of an ERAS program. ERAS was compared to conventional perioperative care. The pooled proportion and the confidence interval (CI) are shown for each outcome. The overlap of the CI suggests similar effect of the interventions studied.Results: Thirteen case series studies with ERAS involving 1,250 patients were compared to six case series with conventional care with a total of 1,429 patients. The pooled, respective proportions for ERAS and conventional care were: mortality, 1.51% [95% CI: 0.0091, 0.0226] and 3.0% [95% CI 0.0183, 0.0445]; and incidence of complications, 3.82% [95% CI 0.0259, 0.0528] and 4.0% [95% CI 0.03, 0.05].Conclusion: This review shows that ERAS and conventional care therapies have similar mortality and complication rates in OSR of AAA.